Effect of a Slow-Release Urea Nanofertilizer on Soil Microflora and Yield of Direct Seeded Rice (Oryza sativa L.) - Yashika Sehgal; Anu Kalia; Buta Singh Dhillon; Gurmeet Singh Dheri (Nitrogen)
Nitrogen fertilizers have a significant impact on the growth of rice. The overuse and inappropriate application of nitrogen fertilizers have resulted in environmental pollution, in addition to subjecting both humans and livestock to negative health hazards. Finding a viable substitute for traditional nitrogen fertilizers is crucial and essential to help improve crop yield and minimize environmental damage. Nano-nitrogen fertilizers offer a possible alternative to traditional fertilizers due to a slow/controlled release of nitrogen. The present work aimed to study the effect of a slow-release urea nanofertilizer on soil ammonical (NH4-N) and nitrate-N (NO3-N) content, culturable soil microflora, and soil enzyme activities in three different soil samples procured from Ludhiana and Patiala districts through a soil column study. Seven treatments, including 0, 50 (75 kg/ha N), 75 (112.5 kg/ha N), and 100% (150 kg/ha N) of the recommended dose (RD) of conventional urea and nano-urea fertilizer were applied. The leachate samples collected from nano-urea treatment exhibited NH4-N for the first two weeks, followed by NO3-N appearance. The higher NH4-N and NO3-N contents in the leachate were recorded for light-textured soil as compared to medium- and heavy-textured soil samples. The soil microbial counts and enzyme activities were recorded to be maximum in light-textured soils. Therefore, this slow-release formulation could be more useful for light-textured soils to decrease applied N-fertilizer losses, as well as for improving the soil microbial viable cell counts and soil enzyme activities. The effect of urea nanofertilizer on the growth and yield of direct-seeded rice (Oryza sativa L.) was also evaluated under field conditions. Both studies were performed independently. Numerically, the highest shoot height, fresh and dry shoot weight, and significantly maximum total chlorophyll, carotenoid, and anthocyanins were recorded in the T2 (100% RDF through nano-urea) treatment. The yield-attributing traits, including the number of filled grains and thousand-grain weight, were also recorded to have increased in T2 treatment. A numerical increase in NPK for plant and grain of rice at 100% RDN through nano-urea was recorded. The soil application of the product exhibited no negative effect on the soil microbial viable cell count on different doses of nano-urea fertilizer. The soil nitrogen fixer viable counts were rather improved in nano-urea treatments. The results reflect that nano-urea fertilizer could be considered as a possible alternative to conventional fertilizer.